RNA sequencing of salivary gland of swiftlet - Looi, Qi Hao; Ideris, Aini; Abu Bakar @ Zakaria, Md Zuki; Omar, Abdul Rahman (Faculty of Veterinary Medicine, Universiti Putra Malaysia, 2015)
Genome mapping of avian species such as chicken, duck and turkey have significant impact on both sosio-economic and ecological due to their importance to agriculture and related industries. However, currently there is limited information available on genetic profiling of swiftlet species. Next-generation sequencing (NGS) based RNA sequencing of salivary gland of Aerodramus fuciphagus and Aerodramus maximus generated reference transcript libraries with 17.4 million and 19.6 million clean reads, respectively. A total of 14,835 genes were predicted and mapped toward various databases. Bioinformatics analysis and further validation studies of these genes my provide valuable information on swiftlet speciation and discovery of biomarker for edible bird nest identification.